2014
DOI: 10.1186/2194-6434-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology and public health: linking human leptospirosis and local hydrological dynamics in Trinidad, West Indies

Abstract: Background: Human leptospirosis is currently one of the most widespread bacterial zoonoses and is the only epidemic-prone infection that can be transmitted directly from contaminated water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 36 publications
(64 reference statements)
5
24
1
3
Order By: Relevance
“…En la pasada década, el interés se concentró en definir las zonas geográficas donde la leptospirosis fue un problema de salud pública y un riesgo potencial para los visitantes (Pappas et al 2008). La magnitud de esta enfermedad infecciosa refleja alta endemicidad, principalmente en la región del Caribe (Batchelor et al 2012, CAREC 2008, Vega-Corredor et al 2014, en la región Central y Sur de América, en el Sureste de Asia y Oceanía (Pappas et al 2008). De acuerdo a esta recopilación de datos, los primeros cinco países con mayor incidencia de casos anuales de leptospirosis : "Análisis espacial y epidemiológico sobre leptospirosis humana en Puerto Rico, 1996", GeoFocus (Artículos), nº 21, p. 227-251.…”
Section: Revisión Bibliográficaunclassified
See 2 more Smart Citations
“…En la pasada década, el interés se concentró en definir las zonas geográficas donde la leptospirosis fue un problema de salud pública y un riesgo potencial para los visitantes (Pappas et al 2008). La magnitud de esta enfermedad infecciosa refleja alta endemicidad, principalmente en la región del Caribe (Batchelor et al 2012, CAREC 2008, Vega-Corredor et al 2014, en la región Central y Sur de América, en el Sureste de Asia y Oceanía (Pappas et al 2008). De acuerdo a esta recopilación de datos, los primeros cinco países con mayor incidencia de casos anuales de leptospirosis : "Análisis espacial y epidemiológico sobre leptospirosis humana en Puerto Rico, 1996", GeoFocus (Artículos), nº 21, p. 227-251.…”
Section: Revisión Bibliográficaunclassified
“…Puerto Rico al ser parte de la región caribeña comparte características ambientales y climatológicas muy similares. Por lo tanto, es importante realizar estudios descriptivos que evalúen y analicen las variaciones geo-temporo-espaciales de la ocurrencia de leptospirosis con factores ambientales y climatológicos similares a la ubicación geográfica (Batchelor et al 2012, Vega-Corredor et al 2014.…”
Section: Revisión Bibliográficaunclassified
See 1 more Smart Citation
“…To do this, we have investigated the spatial distribution of S. mansoni using spatially structured and systematically recorded incidence data (chapter 3). The data was found to be valuable in detecting a spatial pattern of this highly focalized disease with dynamic distribution in time and space such as schistosomiasis (chapter 5), similarly to others water based diseases (Odoi et al, 2003;Osei & Duker, 2008;Vega-Corredor & Opadeyi, 2014). The study demonstrated that schistosomiasis was not distributed randomly and is significantly associated with wetlands and their use (agricultural).…”
Section: Introductionmentioning
confidence: 85%
“…Consequently, there is a clear need to explore the value of other sources of health data and alternative mapping approaches to complement prevalence inventories and support planning and implementation of S. mansoni control programs. For other water based diseases, incidence data from routine health statistics have been successfully used to complement prevalence studies and identify the spatial distribution of a given disease (Odoi et al, 2003;Osei & Duker, 2008;Vega-Corredor & Opadeyi, 2014). Given the availability of good quality spatially structured and systematically collected data at the health facility level, use of such incidence data seems feasible in Rwanda.…”
Section: Introductionmentioning
confidence: 99%